The role of chemokines in the recruitment of progenitor cells into the tumor niche in patients with breast cancer; Перспективы развития фундаментальных наук; Т. 4 : Биология и фундаментальная медицина - Poletika V. S. (2017, 2017)
Заглавие с экрана